2022
DOI: 10.3390/ma15217510
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Tantalum Carbide Using Purified Hexane by Titanium Powder

Abstract: Hexane is a safe, efficient, and cost-effective alternative to other commercial hydrocarbons for gaseous carburization; however, commercial hexane is not sufficiently pure. Titanium powder can remove oxygen-containing impurities from commercial hexane; however, research on the use of titanium powder remains limited. We investigated the purification of hexane using titanium, copper, and aluminum powders and used the purified hexane for the gaseous carburization of tantalum. Ti exhibited lower activation energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Furthermore, from this value, the reduction rate values, k and ln k, could be calculated, and the obtained results are summarized in Table 1. The activation energy for Mg reduction was determined from the plot of ln k and the reciprocal of the reduction temperature, 1/T (Figure 11) [14,[24][25][26]. As shown in Figure 11 The ~50% lower activation energy for Nb-Ti alloy production indicates that the reduction reaction is faster and more effective when a mixed oxide is used.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, from this value, the reduction rate values, k and ln k, could be calculated, and the obtained results are summarized in Table 1. The activation energy for Mg reduction was determined from the plot of ln k and the reciprocal of the reduction temperature, 1/T (Figure 11) [14,[24][25][26]. As shown in Figure 11 The ~50% lower activation energy for Nb-Ti alloy production indicates that the reduction reaction is faster and more effective when a mixed oxide is used.…”
Section: Resultsmentioning
confidence: 99%
“…The nanoparticle powder of TaC can be facilely obtained via several methods with high stability. 32 There are a few papers reported that TaC is compatible with human tissues and body fluids and does not cause a significant immune response. 29,30,33,34 Compared with traditional additives such as BaSO 4 and ZrO 2 , Ta has higher atomic number and higher electron density, producing more photoelectric effect and Compton scattering when interacting with rays, and can effectively absorb and scatter radiation, which helps to improve the barrier ability of radiation, thus enhancing the radiopaque property of bone cement.…”
Section: Introductionmentioning
confidence: 99%